Execution of The Object of Dependent Rights Through Auction Based On The Principle of Proportionality - Tutiek Retnowati; Widyawati Boediningsih; Muh. Gani Irwansyah (Eduvest - Journal of Universal Studies, 2023)
This research was conducted to analyze the granting of credit by the Bank as the creditor to the debtor with land as collateral to the bank if something goes wrong with what was expected. If a credit problem occurs because the debtor is incapacitated or because the debtor has failed in business which results in reduced income so that obligations cannot be fulfilled, the Mortgage Law (UUHT) exists to provide legal certainty for land rights including collateral rights to land. Efforts made by the bank as a creditor if the debtor defaults in order to obtain repayment due to bad credit, namely by executing one of them through an auction. The research method uses normative research with a statutory approach and a concept approach. This research resulted that the execution of mortgage objects through auctions is still not in accordance with the principles of proportionality and legal protection that can be given to debtors, namely repressive and preventive legal protection. In its development, the fact is that in the implementation of executions carried out by creditors, the proceeds from selling mortgage objects through auction execution are often below market prices and do not give the debtor the opportunity sell mortgage objects privately. Regarding this matter, Article 20 paragraph (2) of the Mortgage Law (UUHT) has actually given a sufficient portion of rights the debtor for the sale of mortgage objects according to market prices, but this is limited by the "on agreement" norm, which actually hinders sales under the contract.